Wear and friction of transformation-toughened CMC and MMC; Wear; Vol. 249, iss. 10-11 - Savchenko N. L. Nikolai Leonidovich; Korolev P. V.; Melnikov A. G. Alexander Grigorievich; Tarasov S. Yu. Sergei Yulievich; Kulkov S. N. Sergey Nikolaevich (2001, 2001)
Title screen